Sipunculans of the Caribbean coast of Venezuela and Curaçao - Dean, Harlan K.; Hernández-Ávila, Iván; Cutler, Edward B. (Zootaxa, 2007)
All sipunculan species currently known to occur on the Caribbean coast of Venezuela and Curaçao are reviewed. Included are species previously reported in the primary literature and those collected by Cutler (EBC) in 1987/1988 and Hernández-Ávila (IHA) in 2003/2004. Nineteen species of sipunculans belonging to eleven genera are known from this region. Most specious is the genus Aspidosiphon with seven species and the genus Phascolosoma with three species.